Musykilat Tadris al-Insya’ wa ‘ilajuha Lada Thalabah al-Fashl al-Tsamin bi Madrasah Ma’arif al-Mutawassitah al-Islamiyyah - Fuadi, Faturahman; Inayah, Laila (Institut Agama Islam Negeri (IAIN) Kediri, 2020)
The creation was a representation of the concepts or knowledge or attitudes of the writer. It is worth mentioning here that the construction depicts the linguistic terms that are in the writer's mind. Therefore, the difference between the writing in the creation and the drawing is shown, because the drawing can conceive the meaning, but it is not illustrated On the unity of the language phrases. The problems of the construction of the eighth grade students in the school of Ma’arif Islamic secondary Buana Sakti Batanghari Lambong Oriental, attributed to their weakness in grammatical and grammatical rules, lack of vocabulary for expression, difficulties in organizing ideas in writing or classifying ideas and arranging them in logical order Students may have limited vocabulary to express, but can not express a lack of experience in the construction. Students who are weak in the rules pose a problem when making the construction, such as putting the sentence or placing the pronouns correctly, and when they do not have enough vocabulary to express ideas, To their difficulty in expression, and may write words inappropriate to the subject. This research uses descriptive qualitative research methodsby using questionnaire data analysis, interviews and documentation. data sources obtained from primary and secondary data sources. The pupose of this study was to determine the problem of learning construction and to find solutions in learning for 8 th grade students in Islamic Junior High School 21, Buana Sakti, Batanghari, East Lampung.